PENGARUH PROFESIONALISME APARAT KELURAHAN TERHADAP KUALITAS PELAYANAN PUBLIK DI KELURAHAN MALALAYANG SATU KECAMATAN MALALAYANG KOTA MANADO - Mandey, Donevan Jeremy; Mandey, Jantje; Tulusan, Femmy (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: Improving the quality of public services required of civil servants who are not only in terms of quantity, but also requires the ability professionalism and moral qualities are directly proportional to the demands of society. Human resource development within the ranks of government (public organizations) need to be directed at upgrading professional skills and the development of professional ethics which is accompanied by a spirit of service to the public (community). For the purpose of this study to analyze the influence of professionalism village government officials on the quality of public services in the Village Malalayang One Malalayang District of Manado City. This research method using diagnostic analytic design with descriptive-quantitative method and explanatories survey. The use of quantitative methods and explanatory descriptive-survey possible because this study raised the issue of considerable actual and aims to analyze social phenomena and examine the relationship between the phenomenon or effect. The population in this study were all village officials and community service users in villages Malalayang One Malalayang District of Manado City. The purposive sampling conducted as many as 30 people, consisting of 15 people Malalayang The village government apparatus and the remaining 15 persons from the community of users of services. the results of this study shows there is a strong indication that when village officials increased professionalism (high) will encourage the improvement of the quality of public services. These results are consistent with the results of a simple linear regression analysis to the equation Y = 2.062 + 1.040X, and product moment correlation coefficient r of 0.809. Keyword : Profesionalism, Publik Service Quality